SCHOLARSHIP APPLICATION FOR STUDENT-LEVEL SD (PRIMARY SCHOOL) ON EDUCATION DEPARTMENT AND CULTURAL SUB BRANCH CILEDUG TANGERANG USING MICROSOFT VISUAL BASIC VERSION 6.0 - Sudaryanti Emi; Linda Wahyu Widianti, Skom, MMSI Linda Wahyu Widianti, Skom, MMSI (Jurnal Sistem Informasi, 2002)
Education is very important for human life, but not everyone can feel a decenteducation because of the increasing cost of education. For a little overcome this, thegovernment allocated funds to provide scholarships, which often occurs in theprocess of disbursement delays due to a delay in processing the data. With advancesin computer technology today, we should be eased with a variety of applications thatcan help data-processing activities. Therefore, the authors tried to make anapplication which can speed up data processing.